Responses and adaptations of collembolan communities (Hexapoda: Collembola) to flooding and hypoxic conditions - Marx, Michael Thomas; Wild, Anna-Katharina; Knollmann, Ulrich; Kamp, Günter; Wegener, Gerhard; Eisenbeis, Gerhard (Pesquisa Agropecuaria Brasileira, 2010)
Standard ecological methods (pitfall traps, trunk eclectors and soil cores) were used to evaluate collembolan community responses to different flooding intensities. Three sites of a floodplain habitat near Mainz, Germany, with different flooding regimes were investigated. The structures of collembolan communities are markedly different depending on flooding intensity. Sites more affected by flooding are dominated by hygrophilic and hygrotolerant species, whereas the hardwood floodplain is dominated by mesophilic species. The survival strategies of the hygrophilic and hygrotolerant species include egg diapause and passive drifting. The physiological adaptations to hypoxic conditions of several collembolan species were analyzed using a microcalorimeter. The activities were tested under normoxic and hypoxic/anoxic conditions as well as during post-hypoxic recovery. Lactate was increased after hypoxic intervals in the species studied, suggesting that, in addition to a massive decrease in metabolic rate, a modest glycolytic activity may be involved in the tolerance to hypoxia.